This article was retracted due to scientific plagiarism ((The Effectiveness of Cognitive-Behavioral Therapy on Body Mass Index, the Perception of Physical Image and Self-Concept of Overweight People)) - Hasan Amiri; Kamran Amirian (Iranian Association of Health Education and Health Promotion, 2018)
This article was retracted due to  scientific plagiarism Background and Objective: Considering that obesity is the physical and mental disease, it also reduces the ability of individuals and makes them vulnerable to illness. The purpose of this study was to determine the effect of cognitive-behavioral therapy on body mass index, the perception of physical image and self-concept of overweight individuals. Methods: The research method was a quasi-experimental with pre-test and post-test design including a control group. Sixty men were selected from eligible male and female volunteers referred to Elam nutrition therapy centers and randomly divided into two experimental and control groups. The data collection tools were body mass index, Littleton body image concerns test, and Beck self-concept test, respectively. The experimental group used Cooper's treatment protocol during 24 sessions and 44 weeks in two phases of weight loss (30 weeks) and weight maintenance phase of treatment was 14 weeks. After the end of the sessions, the post-test was carried out. Results: Data analysis was conducted by covariance analysis that showed a significant difference between the body mass index and self-concept of overweight people in the experimental group compared to the control group during the post-test. Cognitive-behavioral therapy was effective in reducing body mass index (p <0/05), the perception of the physical image (p<0/05) and improvement of self-concept (p <0/05) in overweight individuals.   Conclusion: Cognitive behavioral therapy is effective in reducing BMI and perception of physical image and improving the self-concept of high-weight individuals.